2018
DOI: 10.1534/g3.118.200091
|View full text |Cite
|
Sign up to set email alerts
|

Selection on Expected Maximum Haploid Breeding Values Can Increase Genetic Gain in Recurrent Genomic Selection

Abstract: Genomic selection (GS) offers the possibility to estimate the effects of genome-wide molecular markers, which can be used to calculate genomic estimated breeding values (GEBVs) for individuals without phenotypes. GEBVs can serve as a selection criterion in recurrent GS, maximizing single-cycle but not necessarily long-term genetic gain. As simple genome-wide sums, GEBVs do not take into account other genomic information, such as the map positions of loci and linkage phases of alleles. Therefore, we herein prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 31 publications
5
63
0
Order By: Relevance
“…Lehermeier et al (2017b) observed that using UC as a cross selection index increased the short 55 term genetic gain compared to evaluate crosses based on OHV or mean parental GEBV. Similar results 56 have been obtained by simulations in Müller et al (2018) considering the expected maximum haploid 57 breeding value (EMBV) that is akin to the UC for normally distributed and fully additive traits. 58…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Lehermeier et al (2017b) observed that using UC as a cross selection index increased the short 55 term genetic gain compared to evaluate crosses based on OHV or mean parental GEBV. Similar results 56 have been obtained by simulations in Müller et al (2018) considering the expected maximum haploid 57 breeding value (EMBV) that is akin to the UC for normally distributed and fully additive traits. 58…”
Section: Introductionsupporting
confidence: 59%
“…1A). This tendency was also observed in simulations by Müller et al (2018) considering the EMBV approach, 403 akin to the UC for normally distributed additive traits. The UC also showed a higher long term genetic 404 gain at both commercial (G10) and whole progeny level (G) compared to intercross the best candidate 405 parents (PM).…”
Section: Effect Of Usefulness Criterion On Short and Long Term Recurrmentioning
confidence: 58%
See 2 more Smart Citations
“…Applying UCPC within 516 the context of mating design optimization would enable to account for parental 517 complementarity through the use of progeny variation, i.e. within cross variance, as proposed 518 by Shepherd and Kinghorn (1998), Akdemir and Sánchez (2016) and Müller et al (2018).…”
mentioning
confidence: 99%